Genetic diversity and variety composition of cassava on smallscale farms in Uganda: an interdisciplinary study using genetic markers and farmer interviews - Balyejusa Kizito, Elizabeth (Genetica, 2007)
Cassava is a tropical crop and grown for its tuberous starchy roots. In Africa it is mainly cultivated by small-scale farmers who observe, select and name their cassava varieties based on morphology, food, social and economic interest. Here we have used an interdisciplinary approach involving farmer interviews, genetic markers and morphological descriptors to study the composition of cassava varieties on smallscale farms in 11 villages located in three districts in Uganda, the genetic structure within and between these varieties and their morphology. The composition of local, newly introduced and improved varieties differed widely between villages and districts. The Ugandan farmers in our study seemed to adopt improved varieties to a greater extent when there was a nearby market, prevalence of disease epidemics and good extension service. We found considerable genetic variation both within and between cassava varieties though the variation was larger between varieties. However, most local and improved varieties showed predominating genotypes at many loci. Accessions of commonly grown varieties meeting farmers’ preferences could therefore be selected and implemented in future breeding programmes involving development, dissemination and adoption. The like-named varieties in different villages were genetically similar, demonstrating farmers’ ability to differentiate and maintain the same variety over large areas. However, some varieties with different names in different villages showed both genetic and morphological similarity, suggesting that farmers may rename plants when they are introduced into their fields. The large differences found in variety and genetic composition between villages and districts in Uganda may be a result of the diverse needs and growing conditions characteristic for traditional farming system. This suggests that efforts to conserve and increase the genetic diversity in farmers’ fields will require policies tailored to each area
Keywords: Cassava varieties; Crop evolution; Farmers’ management; Genetic differentiation; Manihot esculenta; Morphological variation; Small-scale farmers; SSR markers; Traditional farming system